ELIZA MARIA FERREIRA VERAS DA SILVA - ENGLISH VERSION - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Eliza Maria was a pioneer in mathematics in Brazil, being the first female professor at the Institute of Mathematics and Statistics at the Federal University of Bahia (UFBA) to have a doctorate. She was also the black woman in Brazil with the oldest doctoral degree in mathematics.